An exploratory study of the human resource climate dimensions that influence the development of workplace friendships in the Australian context - Syed Ibrahim, Sharifah Endah (Curtin University, 2014)
Workplace friendships are unique relationships which have been associated with positive outcomes at both the individual and organisational level. The objective in this study is to close the literary gap by empirically investigating the causal effect of human resource (HR) climate dimensions on workplace friendships (WFs) within the Australian context. The results of the study will facilitate an understanding of the scope and impact of HR climate on the opportunity to develop and maintain WFs.